Environmental research and governance in the digital age: results of a horizon scanning for the environment department in tomorrow’s society - Erdmann, Lorenz; Kimpeler, Simone; Gutknecht, Ralph; Cuhls, Kerstin; Rörden, Jan (Broschüren / Umweltbundesamt, 2024)
Digitalisation is profoundly changing our society and therefore also the way in which the environment is researched and governance is carried out. E-government is intended to make administration more efficient and bring it closer to citizens, while new ideas are constantly being implemented in environmental research, such as the ⁠CO2⁠ calculator, apps for sustainable consumption or big data-supported climate simulations. But are these measures already exploiting the full potential that digitalisation holds for the environment department and its environmental research and governance in the digital age? And how will the work of the environment department change when citizens, civil society, companies, science and politics, and therefore society as a whole, undergo major changes as a result of digitalisation?